Pendampingan Siswa Dalam Pencegahan Cyberbulliying - Indiati; paramita (AMMA : Jurnal Pengabdian Masyarakat, 2022)
Bullying that occurs among students is not only done directly but is mostly done indirectly (online). The purpose of this service is to assist students in preventing cyberbullying so that students have an understanding of cyberbullying behavior among students, help students know how to avoid cyberbullying, increase the confidence of students who experience cyberbullying, and prevent students from bullying behavior. The steps in the implementation of this service are the preparation and implementation of (1) initial assessment, (2) provision of material, (3) practical assignment, (4) final assessment. The result of this service is an increase of 57% related to the understanding of cyberbullying for students.